Phenotyping Apathy in Individuals With Alzheimer Disease Using Functional Principal Component Analysis - Zeitzer, Jamie M. (2013)
OBJECTIVES: To determine if there is a specific pattern of gross motor activity associated with apathy in individuals with Alzheimer disease (AD). DESIGN: Examination of ad libitum 24-hour ambulatory gross motor activity patterns. SETTING: Community-dwelling, outpatient. PARTICIPANTS: Ninety-two individuals with AD, 35 of whom had apathy. MEASUREMENTS: Wrist actigraphy data were collected and examined using functional principal component analysis (fPCA). RESULTS: Individuals with apathy have a different pattern of gross motor activity than those without apathy (first fPCA component, p <0.0001, t = 5.73, df = 90, t test) such that there is a pronounced decline in early afternoon activity in those with apathy. This change in activity is independent of depression (p = 0.68, F([1, 89]) = 0.05, analysis of variance). The decline in activity is consistent with an increase in napping. Those with apathy also have an early wake and bedtime (second fPCA component, t = 2.53, df = 90, p <0.05, t test). CONCLUSIONS: There is a signature activity pattern in individuals with apathy and AD that is distinct from those without apathy and those with depression. Actigraphy may be a useful adjunctive measurement in the clinical diagnosis of apathy in the context of AD.